MicroRNA-206: a promising theranostic marker - Novák, Jan; Kružliak, Peter; Bienertová-Vašků, Julie; Slabý, Ondřej; Novák, Miroslav (Theranostics, 2014)
MicroRNAs (miRs) are small non-coding RNAs that negatively regulate gene expression by binding to the 3` untranslated regions (3`UTR) of their target mRNAs. MiRs were shown to play pivotal roles in tissue development and function and are also involved in the pathogenesis of various diseases including cancer. MicroRNA-206, which belongs to the group of so-called "myomiRs", is one of the most studied miRs thus far. In addition to being involved in skeletal muscle development and pathology, it has also been established that it is involved in the pathogenesis of numerous diseases including heart failure, chronic obstructive pulmonary disease, Alzheimer's disease and various types of cancers. The aim of this review is to provide a complex overview of microRNA-206, including regulating its expression, a brief description of its known functions in skeletal muscle and a complex overview of its roles in the biology and pathology of other tissues, emphasizing its significant diagnostic and therapeutic potential.
Keywords: kosterní svaly; biologické přípravky; biologické markery; Biomarkers; Biological Products; Heart Failure; Neoplasms; nádory; Theranostic Marker; lidé; srdeční selhání; Pulmonary Disease, Chronic Obstructive; Muscle, Skeletal; chronická obstrukční plicní nemoc; microRNA-206; Alzheimer Disease; mikro RNA; Alzheimerova nemoc; MicroRNAs; Humans